The Therapeutic Value of Erythropoietin in Preventing the Negative Effects of Methotrexate on the Stomach (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The current study aimed to evaluate any potential protective effects of erythropoietin (Epo) andidentify potential histological adverse changes in the stomach caused by methotrexate (MTX) therapy.Materials and Methods: There were 60 mature albino rats (about 250 g) in the study. Three equal groupsof 20 rats each were created out of the animals. For 9 weeks, the animals in the first control group receivedintraperitoneal injections of normal saline twice a week at a dose of 0.5 mg/kg. For duration of 9 weeks,animals in Group 2 received intraperitoneal injections of MTX hydrate twice a week at a dose of 0.5 mg/kg.The animals in Group 3 were given intraperitoneal injections of MTX hydrate at a dosage of 0.5 mg/kg twicea week for 9 weeks, along with subcutaneous injections of 100 IU/kg recombinant human Epo once a week.Results and Discussion: The stomach tissue’s morphological and histological alterations were evaluated. Thecontents of glutathione peroxidase, superoxide dismutase, glutathione, and IL-2 and IL-6 (interleukin 6) in theserum sample were then determined. Epo demonstrated pronounced antioxidant properties and mitigated MTX’sdeleterious effects on stomach histology. Conclusion: Our findings point to the need for more investigation intothe potential use of Epo as a medication to shield patients from MTX’s side effects.